Electrochemical Generation and Detection of Transient Concentration Gradients in Microfluidic Channels. Theoretical and Experimental Investigations - Abadie, Thomas; Sella, Catherine; Perrodin, Pierre; Thouin, Laurent (Frontiers in Chemistry, 2019)
Transient concentration gradients generated and detected electrochemically in continuous flow microchannels were investigated by numerical simulations and amperometric measurements. Operating conditions including device geometry and hydrodynamic regime were theoretically delineated for producing gradients of various profiles with tunable characteristics. Experiments were carried out with microfluidic devices incorporating a dual-channel-electrode configuration. Under these conditions, high electrochemical performance was achieved both to generate concentration gradients and to monitor their dynamics along linear microchannels. Good agreement was observed between simulated and experimental data validating predictions between gradient properties and generation conditions. These results demonstrated the capability of electrochemical microdevices to produce in situ tunable concentration gradients with real-time monitoring. This approach is versatile for the active control in microfluidics of microenvironments or chemical gradients with high spatiotemporal resolution.